Ideas intuitivas y aprendizaje de las ciencias - Solís Villa, R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
Current research in science education has shown that before any formal science teaching takes place, pupils have already acquired considerable knowledge about natural phenomena. This knowledge differs significantly from the accepted scientific view and interfere with the learning of the subject matter. In this paper, the origin, characteristics and modification of pupils' intuitive ideas will be explored following the PSHG model (PSHG stands for Posner, Strike, Hewson and Gertzog); in terms of this model the process of learning science is a process of conceptual change from one set of concepts to another set, which is incompatible with the previous one.